Investigation and analysis of Hormozgan province\'s fisheries and aquaculture industry innovation ecosystem - Sadegh Samsampour; Ashraf Shahmansoury; Mohammad Hassan Cheraghali; Tahmoures Sohrabi (بوم‌شناسی آبزیان, 2020)
The fishery industry in Hormozgan province has a long history and consists a large part of the economy of this province. The industry, with its many actors, including universities, research centers, small and medium-sized companies, has the potential to be explored as an innovation ecosystem. The concept of innovation ecosystems has been widely considered in recent years and is considered an essential component for enhancing the innovation and economic capacity of enterprises, industries, regions, and nations. Therefore, in the present study, to analyze the innovation ecosystem of the fisheries industry, first, a conceptual model is developed using the literature. Then, with the help of a qualitative research approach, using the content analysis of in-depth and semi-structured interviews with experts in the province's fisheries industry, we identify the actors and the relationships between them and analyze the innovation ecosystem of this industry. Finally, policy proposals are presented to strengthen the ecosystem.